Heart rate variability and acute mountain sickness during the acclimatization period of altitude training camp in elite swimmers - Calderon-Soto, C.; Morales, A. J.; Rodriguez, F. A.; Iglesias, X.; Feriche, B.; Vazguez, J.; Rodriguez-Zamora, L.; Barrero, Z.; Hynynen, E. (Sport Science Research Group, INEFC-Barcelona, 2012)
During altitude training hypoxic stimulus may lead to symptoms of acute mountain sickness and changes in autonomic balance measured by heart rate variability. Our aim was to analyze the classical parameters and the new ones developed by Firstbeat Technologies during the acclimatization period at moderate altitude. Conclusions: Clinical and physiological states during altitude training could be monitored by heart rate variability and symptomatology. Although there is great variability among subjects, new variables as absolute relaxation index show potential usefulness during the acclimatization period of altitude training. Clinical and cardiovascular variables show some delay but both seem to recover at the end of the 1st week. More studies are needed to control other variables such as training load and individual susceptibility.